Design And Construction Of Cocoa Bean Drying Equipment For Regulating Water Content Using The Fuzzy Method - Saputro, Adi Kurniawan; Iyabu, Sissy Rahmatia; Purnamasari, Dian Neipa; Ulum, Miftachul; Ubaidillah, Achmad; Fahmi, Monika Faswia (Jurnal Teknik Elektro Indonesia, 2025)
Indonesia is one of the largest cocoa-producing countries, exporting much of its cocoa to Japan, China, and Malaysia. The export standard for dried cocoa beans is a maximum moisture content of 7%. Traditional sun drying methods in Indonesia do not consistently achieve this standard. Therefore, a cocoa bean dryer using the Mamdani type fuzzy method was designed to control moisture content. This dryer features heaters regulated by dimmers and sensors that monitor temperature and humidity in the drying chamber. The ESP32 microcontroller processes the sensor data and connects to the Internet for control and monitoring via Blynk software, enabling more efficient and faster drying compared to traditional methods. Testing showed the dryer functions as intended. Temperature sensor tests indicated minor variations between sensor and thermogun readings, with an average sensor reading of 42.3°C, thermogun reading of 42.5°C, an average error of 0.4°C, and a 1% error percentage. Humidity sensor tests revealed similar consistency, with an average sensor reading of 46.5%, hygrometer reading of 46.2%, an average error of 0.3%, and a 0.53% error percentage. Load cell tests showed an average sensor reading of 0.32 kg compared to a digital scale reading of 0.33 kg, with an average error of 0.01 kg and a 5.34% error percentage. Each sensor was tested 30 times. Fuzzy control testing yielded satisfactory results, with an average error of 0.4% compared to Matlab results. Moisture content measurements met the export standard. This system is expected to improve the quality and market value of Indonesian cocoa beans.